Association between baseline body mass index and overall survival among patients over age 60 with acute myeloid leukemia. Issue 8 (30th May 2013) - Brunner, Andrew M.; Sadrzadeh, Hossein; Feng, Yang; Drapkin, Benjamin J.; Ballen, Karen K.; Attar, Eyal C.; Amrein, Philip C.; McAfee, Steven L.; Chen, Yi‐Bin; Neuberg, Donna S.; Fathi, Amir T.
<x xml:space="preserve">Abstract</x> Acute myeloid leukemia (AML) is more common and more lethal among patients over the age of 60. Increased body mass index (BMI) has been associated with a higher incidence of various malignancies, including AML. We sought to determine whether patient BMI at the time of AML diagnosis is related to overall survival (OS) among elderly patients. We identified 97 patients with AML diagnosed after the age of 60 and treated with cytarabine‐based induction chemotherapy. The median age was 68 years (range 60–87); 52% of patients were male, and our study population was predominantly white (89% of patients). The median OS for all patients was 316 days (95% CI 246–459). The hazard ratio for mortality was increased among patients with a BMI < 25 compared to BMI ≥ 30 (HR 2.14, P = 0.009, 95% CI 1.21–3.77), as well as with older age (HR 1.76, P = 0.015, 95% CI 1.12–2.79) and with secondary versus de novo disease (HR 1.95, P = 0.006, 95% CI 1.21–3.14). After multivariable analysis, we did not find a significant association between OS and other potential confounders such as coronary artery disease or diabetes among these patients. We conclude that increased BMI was independently associated with improved OS among older AML patients at our institution. Am. J. Hematol. 88:642–646, 2013. © 2013 Wiley Periodicals, Inc.